Gagasan Pemikiran Khaleed Abou El-Fadhl Tentang Islam Moderat, Islam Puritan Dan Cita Ideal Humanisme Islam - Nining Khurrotul Aini (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2020)
Crossing the transformative moment against the setting of a global era, Islam today is marked by a hard struggle between two paradigms of thought. Moderate & puritanical. When there is a vacuum of religious authority in the modern Islamic world, both of them fight over claims to define the meaning of Islamic truth. Khaleed Abou El-Fadl provides a fairly comprehensive map of the two ideas of thought which will play a large role in determining the future of Islam. Starting with a large background that became the battlefield for both in interpreting various aspects of Islamic teachings. Fatwas that refer to religious texts by not paying attention to their historical social context will lose their relevance and urgency in particular if they are taken carelessly and without merit. The offer tried by Khaleed Abou El Fadhl would be important to study and understand and be criticized and finally decided to reject or accept it.